The Women’s Tennis Association (WTA) Multidisciplinary Education and Treatment Protocol for the Female Athlete Triad (1996–2022) - Emily A. Ricker; Kristen J. Koltun; Carol L. Otis; Anna S. Peavler; Mary Jane De Souza (Sports)
Elite female tennis players are among those at high risk for developing the Female Athlete Triad (Triad), characterized by three interrelated conditions: energy deficiency/low energy availability, menstrual dysfunction, and low bone mineral density. From 1996 to 2022, the Women’s Tennis Association (WTA) developed and implemented prevention, education, and management plans for female athletes at risk for, or exhibiting symptoms of, the Triad. This article reviews the WTA Triad protocol, developed in 2018 and utilized through 2022, in collaboration with subject matter experts in the Women’s Health and Exercise Laboratory at The Pennsylvania State University. The WTA Triad protocol (1996–2022) includes prevention and management programs implemented by a multidisciplinary Performance Health Team to include screening for “red flags” during annual physicals or upon clinical presentation of a menstrual problem, bone disorder, or nutritional concern; targeted education for players, coaches, and other support team members with handouts and lectures on nutrition and body image to prevent energy deficiency; and a multidisciplinary protocol to guide treatment and return-to-play decisions. Other sport governing bodies can adopt similar multi-layered programs and practices for their athletes, coaches, and support teams to educate, screen, manage, and help to prevent the development of the Triad.